Visual marking inhibits singleton capture. - Olivers, C; Humphreys, G (2003)
This paper is concerned with how we prioritize the selection of new objects in visual scenes. We present four experiments investigating the effects of distractor previews on visual search through new objects. Participants viewed a set of to-be-ignored nontargets, with the task being to search for a target in a second set, added to the first after 1000ms. This second set could contain a salient feature singleton, defined in terms of its color, orientation, or both color and orientation. When the singleton was a distractor, search was slowed relative to when there was no singleton. Search was facilitated when the singleton was a target. Interestingly, both the interference and facilitation effects were modulated when the preview shared features with the singleton. Follow-up experiments showed that this reduction of singleton effects was not due to: (i) low-level sensory aspects of the displays, (ii) increased heterogeneity in the search set in the preview condition, or (iii) color-based grouping of old and new items. Instead, we suggest that there is an inhibitory carry-over from the first to the second set of items based on feature similarity. We suggest the suppression stems from a process termed visual marking, which suppresses irrelevant visual objects in anticipation of more relevant new objects (Watson and Humphreys, 1997). The findings argue against alternative explanations such as the automatic capture by abrupt new onsets account.